Glimpses of Hospitals / Nursing Homes having Cardiac Care facilities in Kathmandu Valley - Malla, Rabi (Nepalese Heart Journal, 2000)
This is the oldest hospital in Nepal and is run by His Majesty’s Government of Nepal. It was established about hundred and ten years ago. It is located in the heart of the capital, Kathmandu with facilities for almost all aspects of surgery and medicine. The cardiac unit is headed by Dr. AB Upadhyaya, a prominent cardiologist of Nepal and CTVS unit is headed by Dr. D.P. Pokharel, a prominent cardiac surgeon who is also the Executive Director of SGNHC. The hospital has ICU/CCU facilities, 24 hrs emergency service. It also provides echocardiogram, holter monitoring and TMT services, closed and openheart surgeries are done regularly and CABG was done for the first time in Nepal on 19" June 2000 by Dr. D. P. Pokharel and is continuing on a regular basis.